The flounder - Grass, Gèunter 1927-2015 (Secher & Warbury, 1978)
Based loosely on Grimm's The Fisherman and his Wife, this triumphant blend of folk tale and contemporary story takes place over the course of nine months, during which the wife of the narrator becomes pregnant and is regaled with tales of the various cooks the fisherman has met throughout his life. The emerging themes of the novel expose the periods when men made history and women's contributions went largely, in some cases gravely, unrecognized. Inventive, imaginitive and irreverent, this humorous, fundamentally brilliant novel highlights the value of modern-day myth and timeless legend.